2012
DOI: 10.1007/s11914-012-0119-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet in Osteoporosis Prevention and Management

Abstract: Diet, a modifiable osteoporosis risk factor, plays an important role in the acquisition and maintenance of bone mass. The influence of diet on bone begins in childhood; even maternal diet can influence bone mass in the offspring. A good general nutritional status and adequate dietary protein, calcium, vitamin D, fruits, and vegetables have a positive influence on bone health, while a high caloric diet and heavy alcohol consumption have been associated with lower bone mass and higher rates of fracture. The evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 43 publications
1
35
0
1
Order By: Relevance
“…This is likely to have a negative impact on bone health as recent evidence has indicated that both gastrointestinal calcium absorption and bone mineralisation are impeded in vitamin D insufficiency. Furthermore, vitamin D has been shown to be protective against falls, thus reducing fracture risk further [10]. Our observations are supported by a number of previous studies which have demonstrated an association between chronic alcoholism and low circulating levels of vitamin D [3,12].…”
Section: Study Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…This is likely to have a negative impact on bone health as recent evidence has indicated that both gastrointestinal calcium absorption and bone mineralisation are impeded in vitamin D insufficiency. Furthermore, vitamin D has been shown to be protective against falls, thus reducing fracture risk further [10]. Our observations are supported by a number of previous studies which have demonstrated an association between chronic alcoholism and low circulating levels of vitamin D [3,12].…”
Section: Study Findingssupporting
confidence: 89%
“…Additionally, we have shown that dietary calcium intake was often low (but extremely variable) in this group; one alcoholic woman was receiving a daily calcium intake as low as 35mg. Although there is no consensus on the appropriate daily calcium dose different organisations recommend between 700mg in the UK and 1300mg in Australia and New Zealand [10]. Inadequate dietary calcium intake results in secondary hyperparathyroidism, which in turn increases bone turnover and accelerates bone loss.…”
Section: Study Findingsmentioning
confidence: 99%
“…These include calcium, vitamin D and proteins, as well as other nutrients such as potassium, magnesium and vitamin K, which may also be related to benefits for bone health. 9 These nutrients initially originate from a suitable food intake. In the women analyzed the parameters relating to food consumption denoted a nutritional imbalance in terms of the actual situation of bone demineralization presented by the sample.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous other nutrients that may infl uence bone metabolism such as copper, zinc, vitamin C, and protein, but there is no fi rm evidence that supplementation of any will infl uence bone mass, even in the general population [ 121 ]. Particular attention to nutrition in the stroke survivor to achieve a healthy balanced intake is prudent for multiple reasons, including bone health.…”
Section: Nutritionmentioning
confidence: 99%